Nanoscale mapping of intrinsic defects in single-layer graphene using tip-enhanced Raman spectroscopy. Issue 53 (9th June 2016) - Su, Weitao; Kumar, Naresh; Dai, Ning; Roy, Debdulal
Abstract : Non-gap TERS with a contrast of 8.5 enables TERS mapping of graphene's intrinsic defect with a spatial resolution of 20 nm. Abstract : Non-gap mode tip-enhanced Raman spectroscopy (TERS) is used for the first time to successfully map the intrinsic defects in single-layer graphene with 20 nm spatial resolution. The nanoscale Raman mapping is enabled by an unprecedented near-field to far-field signal contrast of 8.5 at the Ag-coated TERS tip-apex. These results demonstrate the potential of TERS for characterisation of defects in single-layer graphene-based devices at the nanometre length-scale.